Teachers' Perceptions And Experiences Implementing Independent Curriculum In Indonesian Madrasahs - Adiyani, Rafiqatul; Anwar, Moh; Abidin, Zainal (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study explores teachers’ perceptions and experiences in implementing the Merdeka Curriculum at Madrasah Aliyah Zainul Bahar Wringin, Bondowoso, East Java. Using a qualitative phenomenological approach, the study aims to understand educators' lived experiences in adapting to curriculum changes. Participants, selected through purposive sampling, included the principal, the vice principal for curriculum affairs, and several subject teachers. Data collection methods consisted of semi-structured interviews, document analysis, and non-participant classroom observations. Thematic analysis, based on Braun and Clarke’s framework, guided the data analysis process. This included familiarization with the data, coding, theme development, theme review and definition, and the construction of a thematic narrative. The goal was to identify patterns of meaning in teachers’ experiences with curriculum implementation. To ensure validity, the study employed source triangulation, member checking, and rich contextual descriptions to enhance transferability. Findings show that teachers generally responded positively to the Merdeka Curriculum, recognizing its potential to integrate traditional knowledge with 21st-century skills. Nonetheless, challenges were noted, including limited technological resources, time constraints for differentiated instruction, and inadequate professional development. Teachers emphasized the importance of embedding character and religious values within the curriculum. The study recommends enhancing institutional support through visionary leadership and sustained teacher training. Future research should investigate implementation across different types of madrasahs and compare practices between urban and rural areas to develop a broader understanding of curriculum reform dynamics in the Indonesian education system.